2016
DOI: 10.1089/scd.2015.0305
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Stem Cells: Podocyte Differentiation and Potential for the Treatment of Alport Syndrome

Abstract: 27Alport syndrome is a hereditary glomerulopathy caused by a mutation in type 28 IV collagen genes, which disrupts glomerular basement membrane, leading to 29 progressive glomerulosclerosis and end-stage renal failure. There is at 30 present no cure for Alport syndrome and cell-based therapies offer promise to 31 improve renal function. Here, we found that human first trimester fetal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Instead, they confirm that OCT4A is not expressed in hAFSCs expanded in vitro in non-pluripotent conditions. Interestingly, we have reported that SS-hAFSCs may be more plastic than their postnatal counterparts since when they are cultivated in pluripotent conditions in the presence of valproic acid (VPA), they up-regulated OCT4A expression and reverted to functional bona fide pluripotency by reactivating the OCT4-downstream pluripotent pathway 27,31,40 . This suggests that despite OCT4A being downregulated, DNA conformation at the epigenetic level might be permissive to OCT4A reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they confirm that OCT4A is not expressed in hAFSCs expanded in vitro in non-pluripotent conditions. Interestingly, we have reported that SS-hAFSCs may be more plastic than their postnatal counterparts since when they are cultivated in pluripotent conditions in the presence of valproic acid (VPA), they up-regulated OCT4A expression and reverted to functional bona fide pluripotency by reactivating the OCT4-downstream pluripotent pathway 27,31,40 . This suggests that despite OCT4A being downregulated, DNA conformation at the epigenetic level might be permissive to OCT4A reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Some new drugs have entered clinical trials, such as bardoxolone methyl (Phase II/III) and RG-012 (effect on microRNA-21 interference, Phase II). Other therapies that have thus far been reported to show effects by in vivo and in vitro trials are as follows: (1) treatment with stem cells [42] and (2) treatment to control intracellular signal transduction (USAG-1) [43]. Further expected treatments are as follows: (1) nonsense read-through therapy [44] and (2) exon skipping therapy with antisense oligonucleotides or chemical compounds [45, 46].…”
Section: Treatmentmentioning
confidence: 99%
“…The experimental approaches to reduce renal damage in Alport mice included angiotensin-converting enzyme inhibition, 26 angiotensin-converting enzyme 2 or pentraxin-2 administration, 27-29 endothelin A receptor antagonism, 30 integrin-blockade, 31,32 anti-microRNA-21 oligonucleotide treatment, 33 transforming growth factor-beta antagonism, 31 uterine sensitization-associated gene-1 depletion, 34 CC chemokine receptor 1 antagonism, 35,36 lymphocyte depletion, 37 stem cell administration, [38][39][40] statin administration, 41 and manipulating podocytes to inducibly overexpress collagen a3a4a5(IV) heterotrimers. 42 The degree of protection from renal fibrosis was rather variable in these studies.…”
Section: Discussionmentioning
confidence: 99%